2019
DOI: 10.1021/acsnano.9b00165
|View full text |Cite
|
Sign up to set email alerts
|

Few-Layered Boronic Ester Based Covalent Organic Frameworks/Carbon Nanotube Composites for High-Performance K-Organic Batteries

Abstract: Organic electrodes for low-cost potassium ion batteries (PIBs) are attracting more interest by virtue of their molecular diversity, environmental friendliness, and operation safety. But the sluggish potassium diffusion kinetics, dissolution in organic electrolyte, poor electronic conductivity, and low reversible capacities are several drawbacks compared with inorganic counterparts. Herein, the boronic ester based covalent organic framework (COF) material is successfully prepared on the exterior surface of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
214
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 250 publications
(228 citation statements)
references
References 40 publications
4
214
0
Order By: Relevance
“…The galvanostatic intermittent titration technique (GITT) further investigated the dynamic/thermodynamic behavioral characteristics of BOC@CNT/S electrodes (Figure e). From an equation in the previous reports, the D Li+ of two electrodes can be calculated and displayed in Figure f. It is obviously observed that the lithium ion diffusion coefficients for the BOC@CNT/S electrode (1.97 × 10 −9 to 1.36 × 10 −7 cm 2 s −1 ) are higher than those of BOC/CNT/S (2.77 × 10 −11 to 2.22 × 10 −8 cm 2 s −1 ) during the discharging process.…”
Section: Resultsmentioning
confidence: 92%
“…The galvanostatic intermittent titration technique (GITT) further investigated the dynamic/thermodynamic behavioral characteristics of BOC@CNT/S electrodes (Figure e). From an equation in the previous reports, the D Li+ of two electrodes can be calculated and displayed in Figure f. It is obviously observed that the lithium ion diffusion coefficients for the BOC@CNT/S electrode (1.97 × 10 −9 to 1.36 × 10 −7 cm 2 s −1 ) are higher than those of BOC/CNT/S (2.77 × 10 −11 to 2.22 × 10 −8 cm 2 s −1 ) during the discharging process.…”
Section: Resultsmentioning
confidence: 92%
“…[ 22 ] Therefore, Wang and co‐workers proposed a COF‐10@CNT as anode materials for PIBs, where a boronic ester based covalent–organic framework (COF‐10) was in situ grown on the exterior surface of CNTs ( Figure 14 a,b). [ 120 ] Benefiting from its hierarchical pore structure of COF‐10, a sufficient void space was presented to relieve the volume expansion/contraction during potassiation/depotassiation, resulting in a stable performance (Figure 14c). The discharge/charge curves almost overlapped even after 100, 200, 300, 400, and 500 cycles, indicating the stability of electrode structure and excellent reversible electrochemical behaviors (Figure 14c).…”
Section: Applications In Other Advanced Batteriesmentioning
confidence: 99%
“…Inspired by the existing pioneering work involving graphite, tremendous efforts have been devoted to this area of research. To date, several categories of materials are verified to be effective for potassium storage in terms of anodes, including carbon nanophases (eg, hard carbon, graphite, and heteroatom‐doped carbon), alloy‐type (semi‐)metals (eg, Sn, Bi, Sb, and P), metal oxides (eg, Nb 2 O 5 , SnO 2 , Fe x O, and Sb 2 MoO 6 )/sulfides (eg, MoS 2 , VS 2 , SnS 2 , and Sb 2 S 3 ) and phosphides (eg, FeP, CoP, Sn 4 P 3 , and GeP 5 ), sylvite compounds (eg, KVPO 4 F, K 2 V 3 O 8 , KTi 2 (PO 4 ) 3 , and K x Mn y O z ), metal‐organic composites (eg, Co 3 [Co(CN) 6 ] 2 and K 1.81 Ni[Fe(CN) 6 ] 0.97 ·0.086H 2 O), and pure organic polymers (eg, boronic ester, fluorinated covalent triazine, perylene‐tetracarboxylate, perylenetetracarboxylic diimide, azobenzene‐4,4′‐dicarboxylic acid potassium, 2,2′‐azobis[2‐methylpropionitrile], and poly[pyrene‐ co ‐benzothiadiazole]). However, most carbon materials barely deliver reversible capacities exceeding 300 mAh g −1 despite their excellent electrochemical cyclability.…”
Section: Introductionmentioning
confidence: 99%